Augmented Reality for Subsurface Utility Engineering, Revisited - Hansen, Lasse H (IEEE transactions on visualization and computer graphics, 2021)
Civil engineering is a primary domain for new augmented reality technologies. In this work, the area of subsurface utility engineering is revisited, and new methods tackling well-known, yet unsolved problems are presented. We describe our solution to the outdoor localization problem, which is deemed one of the most critical issues in outdoor augmented reality, proposing a novel, lightweight hardware platform to generate highly accurate position and orientation estimates in a global context. Furthermore, we present new approaches to drastically improve realism of outdoor data visualizations. First, a novel method to replace physical spray markings by indistinguishable virtual counterparts is described. Second, the visualization of 3D reconstructions of real excavations is presented, fusing seamlessly with the view onto the real environment. We demonstrate the power of these new methods on a set of different outdoor scenarios